2021
DOI: 10.1021/acsaem.1c00810
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Investigation for Bandgap Engineering of Wide Bandgap Triple Cation Perovskite

Abstract: Perovskite solar cells have shown their potential for multijunction applications due to their tunable bandgap. This research focuses on triple cation (3C) wide bandgap perovskites ranging from 1.6 to 1.76 eV, an ideal bandgap choice for 2-terminal tandems. The bandgap is changed via the X-site substitution of iodine (I) with bromine (Br) and via cation substitution, with various concentrations of cesium (Cs), methylammonium (MA), and formamidinium (FA). As a result, it is seen that cation engineering is a viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The bandgaps of Cs-FA-MA based HOIPs could be adjusted to the ideal range 1.60–1.76 eV for the top part in tandem cells as well. For instance, the candidates Cs 0.392 FA 0.016 MA 0.592 Cr 0.383 Sr 0.347 Sn 0.270 Br 1.171 I 1.829 , and Cs 0.445 FA 0.161 MA 0.394 Pd 0.508 Cr 0.228 Sn 0.263- Br 1.094 I 1.906 , were found with 1.67 eV bandgap, which were non-Pb substitutes of Cs 0.15 FA 0.17 MA 0.68 PbBr 0.6 I 2.4 investigated by Sala et al 38 And 136 Cs-FA-MA based candidates are listed in Table S10 . As for the HOIPs with bandgap 1.20 eV, 39 41 the non-Pb candidates MA 0.815 FA 0.185 Sn 0.927 Ge 0.073 I 3 (1.22 eV) and MA 0.861 FA 0.139 Sn 0.914 Ge 0.086 I 3 (1.22 eV) were found, as compared to the experimental samples, e.g., FA 0.55 MA 0.45 Sn 0.55 Pb 0.45 I 3 (1.24 eV), 42 FA 0.5 MA 0.5 Sn 0.5 Pb 0.5 I 3 (1.20 eV), 43 and FA 0.83 Cs 0.17 Pb 0.3 Sn 0.7 I 3 (1.23 eV).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The bandgaps of Cs-FA-MA based HOIPs could be adjusted to the ideal range 1.60–1.76 eV for the top part in tandem cells as well. For instance, the candidates Cs 0.392 FA 0.016 MA 0.592 Cr 0.383 Sr 0.347 Sn 0.270 Br 1.171 I 1.829 , and Cs 0.445 FA 0.161 MA 0.394 Pd 0.508 Cr 0.228 Sn 0.263- Br 1.094 I 1.906 , were found with 1.67 eV bandgap, which were non-Pb substitutes of Cs 0.15 FA 0.17 MA 0.68 PbBr 0.6 I 2.4 investigated by Sala et al 38 And 136 Cs-FA-MA based candidates are listed in Table S10 . As for the HOIPs with bandgap 1.20 eV, 39 41 the non-Pb candidates MA 0.815 FA 0.185 Sn 0.927 Ge 0.073 I 3 (1.22 eV) and MA 0.861 FA 0.139 Sn 0.914 Ge 0.086 I 3 (1.22 eV) were found, as compared to the experimental samples, e.g., FA 0.55 MA 0.45 Sn 0.55 Pb 0.45 I 3 (1.24 eV), 42 FA 0.5 MA 0.5 Sn 0.5 Pb 0.5 I 3 (1.20 eV), 43 and FA 0.83 Cs 0.17 Pb 0.3 Sn 0.7 I 3 (1.23 eV).…”
Section: Resultsmentioning
confidence: 86%
“…We also expanded our studies to several specific HOIP chemical systems to provide potential candidates for experimental researchers. For example, from our searching results, we found that the candidates Cs 0.334 FA 0.266 MA 38 And 136 Cs-FA-MA based candidates are listed in Table S10. As for the HOIPs with bandgap 1.20 eV, 39−41 the non-Pb candidates M A 0 .…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure c, the J SC calculated by external quantum efficiency (EQE) is basically the same as the actual measured J SC , and the error is within 5%. In addition, Figure d shows the stable output of the PCE and J SC of devices without and with F-type pseudo-halogen additives under continuous illumination at the maximum power point (MPP) for more than 500 s. Figure e–g and Table S5 summarize the V OC , FF, and PCE of the reported WBG PSCs with a band gap of 1.63–1.72 eV (the red ball is the data of this work). ,, ,,,,, Figure h and i show the stability test of the devices at a temperature of 85 °C and a humidity of 50–60%, respectively. The results show that the stability of the devices with F-type pseudo-halogen additives is much greater than that of the control devices, which suggests that the addition of additives helps to improve the stability of the devices.…”
Section: Resultsmentioning
confidence: 93%
“… 31 On the other hand, excess of TOAB might be detrimental as seen in the poorer grains and by the possible change of the band gap of the fabricated perovskite. 32 …”
Section: Resultsmentioning
confidence: 99%